Buffering role of locus of control on stress among the college/university teachers of Bahawalpur - Aqeel Ahmad Khan; Muhammad Saleem; Raheela Shahid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
The present research is aimed to ascertain the role of locus of control in mediating or coping on various degree/levels of stress among the college/university teachers of Bahawalpur. For that purpose a sample of N=200 male/female college/university teachers was selected by convenient sampling. Research tools, Locus of control by Julian Rotter (1966) and Stress questionnaire by International Stress Management Association UK, (2009) were administered for data collection. After the collection of data it was analyzed by SPSS. The results shows that the teachers identified with internal locus of control reveal low level of stress as contrast to the teachers with external locus of control. The study also confirms that high internal locus of control determines high coping and mediating ability of stress among the teachers. The study also pointed out that the teachers with external locus of control were more incline or prone to stress. Furthermore, Pearson and Spearman's Correlation results at significant level of .000 show that both variables are highly correlated. Similarly, overall Mean of locus of control and Coefficient of variation reveals the high consistency role in relation with stress.
Keywords: 330; Locus of control; Stress; External locus of control; Internal locus of control; Coping ability; Mediating or Buffering role